Maternal height and child mortality in 42 developing countries. - Monden, C; Smits, J (2009)
Previous research reports mixed results about the association between maternal height and child mortality. Some studies suggest that the negative association might be stronger in contexts with fewer resources. This hypothesis has yet not been tested in a cross-nationally comparative design. We use data on 307,223 children born to 194,835 women in 444 districts of 42 developing countries to estimate the association between maternal height and child mortality and test whether this association is modified by indicators at the level of the household (like sex, age and twin status of the child and socio-economic characteristics of the mother and her partner), district (regional level of development, public health facilities and female occupational attainment) and country (GDP per capita). We find a robust negative effect of logged maternal height on child mortality. The effect of maternal health is strongest for women with least education and is more important in the first year after birth and for twin births. The indicators of development at the district and country level do not modify the effect of maternal height.